Thermal stability of hexamethyldisiloxane and octamethyltrisiloxane. (15th December 2018) - Keulen, L.; Gallarini, S.; Landolina, C.; Spinelli, A.; Iora, P.; Invernizzi, C.; Lietti, L.; Guardone, A.
Abstract: A thermal stability test-rig for organic Rankine cycles working fluids was designed and commissioned at the Laboratory of Compressible-fluid dynamics for Renewable Energy Applications (CREA Lab) of Politecnico di Milano, in collaboration with the University of Brescia. The set-up is composed by a vessel containing the fluid, heated for about 80 h at a constant stress temperature. During the test, the pressure is monitored to detect thermal decomposition of the fluid. After the test, the vessel is placed in a thermal bath, where the vapor pressure is measured at different values of temperature lower than the stress temperature and critical temperature and is compared to that obtained before the fluid underwent thermal stress. If departure from the initial fluid behavior is observed, thermal decomposition occurred and a chemical analysis of the sample is carried out on both liquid and vapor phase using gas chromatography and mass spectrometry. Experimental results are reported for the pure siloxane fluids MM (Hexamethyldisiloxane, C 6 H 18 OSi 2 ) and MDM (Octamethyltrisiloxane, C 8 H 24 O 2 Si 3 ), showing that limited but appreciable decomposition is occurring at 240 °C and 260 °C respectively.